Fabrication of g-C3N4and a promising charcoal property towards enhanced chromium(VI) reduction and wastewater treatment under visible light - Suphatchaya Lamkhao (2018)
© 2017 Elsevier Ltd The visible light driven photoactivity of g-C 3 N 4 can be enhanced using charcoal as a supporter. Charcoal/g-C 3 N 4 composite materials were prepared by the simultaneous thermal condensation of melamine and charcoal. The effect of different atmospheres (O 2 , air, and argon) on the reaction was investigated. The effect of different weight ratios of charcoal to melamine (1:1 and 1:4 wt%) was also investigated. The physical properties of the charcoal/g-C 3 N 4 materials were analyzed using XRD, SEM, TEM, XPS, BET and FTIR techniques. It was found that an oxidation reaction of charcoal and g-C 3 N 4 during preparation greatly affected the photoactivity. A composite of charcoal:melamine (1:4 wt%) prepared under an air atmosphere provided good photooxidation of methylene blue; whereas a composite of charcoal:melamine (1:4 wt%) prepared under an oxygen atmosphere exhibited good photoreduction of chromium (VI).